1998
DOI: 10.1038/sj.mp.4000453
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a chromosome 2p13–14 schizophrenia susceptibility locus in families from Palau, Micronesia

Abstract: A large multiplex schizophrenia pedigree ascertained from the Micronesian nation of Palau was genotyped with 406 microsatellite DNA markers evenly distributed throughout the genome. Assuming autosomal dominant inheritance, the highest genome-wide lod scores were found for DNA loci mapping to 2p13-14; the maximum lod score was 2.17 (theta = 0.05) at D2S441. A nonparametric APM analysis was also suggestive at D2S441 (APM score = 2.96, P = 0.011). Of the 14 affected cases in this extended family, eight share a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…This signal corresponds to that reported in Coon et al 25 for two point analysis. Again this signal reflects extensive haplotype-sharing, in this case more than half of the schizophrenics share a 25 cM haplotype.…”
Section: Molecular Psychiatrysupporting
confidence: 91%
See 3 more Smart Citations
“…This signal corresponds to that reported in Coon et al 25 for two point analysis. Again this signal reflects extensive haplotype-sharing, in this case more than half of the schizophrenics share a 25 cM haplotype.…”
Section: Molecular Psychiatrysupporting
confidence: 91%
“…Multipoint linkage analysis continued to lend some support to 2p, with LOD = 2.2 near D2S393 (80.2cM) under a dominant model. In the earlier analysis, 25 the maximum two-point LOD score (LOD = 2.17) occurred at D2S441, roughly 6 cM away from D2S393.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…MDH1 is located at chromosome 2p13-14. Suggestive linkages in the region of 2p13-14 to schizophrenia (25,26) and to bipolar disorders (27) have been reported. A large meta-analysis of schizophrenia linkage studies showed one region to be highly significant (2p11.1-q21.1), which met the criterion for genome-wide significance (28).…”
Section: Mdh1mentioning
confidence: 99%